Petroleum law in Nigeria : arrangements for upstream operations - Oche, Patrick Ndubisi (Jos, Nigeria : Heirs Great Commission, 2004)
Concerned with the analysis of the legislative provisions that govern the exploitation of petroleum resources in Nigeria. Current legislation in force in respect of upstream petroleum operations in Nigeria are included as appendices.
"First published in 2003."
Includes bibliographical references and index.
oif 04/03/15
Loan
Keywords: Petroleum law and legislation -- Nigeria; Petroleum industry and trade -- Nigeria; Natural resources -- Nigeria -- Management